N-Methylamide-structured SB366791 derivatives with high TRPV1 antagonistic activity: toward PET radiotracers to visualize TRPV1. Issue 10 (13th September 2022) - Kida, Tatsuya; Takahashi, Nobuaki; Mori, Masayuki X.; Sun, Jiacheng H.; Oota, Hideto; Nishino, Kosuke; Okauchi, Takashi; Ochi, Yuta; Kano, Daisuke; Tateishi, Ukihide; Watanabe, Yasuyoshi; Cui, Yilong; et al.
Abstract : N -Methylamide derivatives of SB366791 show higher antagonistic activity against TRPV1 compared with SB366791. 11 C- and 18 F-labeled radiotracers of these derivatives were synthesized, and PET imaging studies using rats were performed. Abstract : Transient receptor potential cation channel subfamily V member 1 (TRPV1)-targeted compounds were synthesized by modifying the structure of SB366791, a pharmaceutically representative TRPV1 antagonist. To avoid amide–iminol tautomerization, structurally supported N -methylated amides ( i.e., 3-alkoxy-substitued N -meythylamide derivatives of SB366791) were evaluated using a Ca 2+ influx assay, in which cells expressed recombinant TRPV1 in the presence of 1.0 μM capsaicin. The antagonistic activities of N -(3-methoxyphenyl)- N -methyl-4-chlorocinnamamide (2 ) (RLC-TV1004) and N -3-(3-fluoropropoxy)phenyl- N -methyl-4-chlorocinnamamide (4 ) (RLC-TV1006) were found to be approximately three-fold higher (IC50 : 1.3 μM and 1.1 μM, respectively) than that of SB366791 (IC50 : 3.7 μM). These results will help reinvigorate the potential of SB366791 in medicinal chemistry applications. The 3-methoxy and 3-fluoroalkoxy substituents were used to obtain radioactive [ 11 C]methoxy- or [ 18 F]fluoroalkoxy-incorporated tracers for in vivo positron emission tomography (PET). Using the 11 C- or 18 F-labeled derivatives, explorative PET imaging trials were performed in rats.